2022
DOI: 10.18203/issn.2455-4529.intjresdermatol20221199
|View full text |Cite
|
Sign up to set email alerts
|

A cross-sectional study of cutaneous changes during pregnancy in a tertiary care hospital in Northern India

Abstract: <p class="abstract"><strong><span lang="EN-US">Background: </span></strong><span lang="EN-US">Women undergo profound changes during pregnancy, making them susceptible to a number of dermatological manifestations. We aimed to determine the frequency and pattern of skin changes during pregnancy.</span></p><p class="abstract"><strong><span lang="EN-US">Methods: </span></strong><span lang="EN-US">A cross-sectional observational stu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
0
1
Order By: Relevance
“…16 Chaudhary et al showed a similar incidence of tinea corporis (7.2%) being more common in fungal infections but scabies was found to be in (3.8%) of patients in their study. 23 Panicker et al showed a similar infection rate of genital warts and herpes genitalis being (1%) whereas in our study it was less than (1%). 3 Infections were more common because of the decreased cellular immunity during pregnancy.…”
Section: Pathological Non-specific Dermatosescontrasting
confidence: 51%
“…16 Chaudhary et al showed a similar incidence of tinea corporis (7.2%) being more common in fungal infections but scabies was found to be in (3.8%) of patients in their study. 23 Panicker et al showed a similar infection rate of genital warts and herpes genitalis being (1%) whereas in our study it was less than (1%). 3 Infections were more common because of the decreased cellular immunity during pregnancy.…”
Section: Pathological Non-specific Dermatosescontrasting
confidence: 51%